Synthesis and Advanced NMR Characterization of Ordered 3D Reticular Materials with PolySilicate Nodes and Hydrophobic OrganoSilicone Linkers - Jamoul, Jelle; Radhakrishnan, Sambhu; Houlleberghs, Maarten; Chandran, C. Vinod; Vits, Aline; Weckx, Pasquinel; Smet, Sam; Arenas Esteban, Daniel; Bals, Sara; Martens, Johan A.; Breynaert, Eric (Molecules (Basel, Switzerland), 2025)
This work describes the synthesis of ordered 3D siloxane-silsesquioxane reticular materials with silicate D4R cubes (Si8O208−), harvested from a sacrificial tetrabutylammonium cyclosilicate hydrate (TBA-CySH) precursor, interlinked with octyl and dicyclopentyl (Cp2) hydrocarbon functionalities in a one-step synthesis with organodichlorosilanes. Advanced solid-state NMR spectroscopy allowed us to unravel the molecular order of the nodes and their interconnection by the silicone linkers. In the case of octyl-methyl silicone linkers, changing the silane-to-silicate ratio in the synthesis allowed for tuning the length of the linker between the nodes. With dicyclopentyl linkers, the addition of dimethyldichlorosilane was essential to enable the formation of a reticular network. The resulting materials contained mixed, dimeric silicone linkers, i.e., Si8-O-Si(Me2)-O-Si(Cp2)-O-Si8.